Identifying Typical Presentations of Vitamin B-12 Deficiency among Individuals Attending Tertiary Care Hospital in Central Gujarat: A Case Control Study - Sangita V. Patel; Alpesh B. Makwana; Archana U. Gandhi; Latika T. Chugh; Vipul Bhavsar (Indian Association of Preventive and Social Medicine, 2024)
inadequate intake leads to haematological and neurological disorders. Objective:To determine the symptoms and signs associated with Vitamin B12 deficiency. Method: A case control study was conducted at the medicine department of tertiary care hospital. Patients visiting hospital with serum Vitamin B12 level below 200pg/ml were labelled as cases and more than 200 pg/ml were labelled as controls, irrespective of signs and symptoms of Vitamin B 12 deficiency.Controls were matched for age to minimize confounding. 160 cases and 160 controls were selected. Pretested semi structured questionnaire was used to identify signs and symptoms of Vitamin B12 deficiency among cases and controls. Chi square test was applied for each symptom between cases and control, of which 10 were significant (p<0.05). ROC curve was plotted for the 10 symptoms to check their usefulness for diagnosing vitamin B12 deficiency. Results: Area-Under Curve (AUC) was maximum under knuckle pigmentation (0.794), (Positive Likelihood Ratio (PLR)=3.24) followed by poor memory (0.684), (PLR=3.25) tingling and numbness (0.624), (PLR=1.84) and dizziness (0.605), (PLR=1.38) in respective order. Whereas fatigue, sore and swollen tongue, pale skin, breathlessness, palpitation, insomnia, memory loss were not associated with Vitamin B12 deficiency(p>0.05).Conclusion: Presence of knuckle pigmentation, poor memory, tingling and numbness, and dizziness can be defined as hallmarks of Vitamin B12 deficiency and can be used to predict and start Vitamin B12 supplementation.